2018
DOI: 10.1002/dmrr.3003
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of early‐pregnancy risk factors for gestational diabetes in polycystic ovarian syndrome

Abstract: Our study established strong association of multiple early-pregnancy risk factors with development of GDM in PCOS women. These risk factors are predominantly related to the regulation of glucose, lipid, and androgen metabolism. Among these factors, FPG, non-high-density lipoprotein-cholesterol, and SHBG, predict incident GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
2
19
0
1
Order By: Relevance
“…Although some studies have shown otherwise 37 , the incidence of GDM, pregnancy-related hypertension and neonatal hypoglycemia is higher in women with PCOS diagnosed [38][39][40] . Glucose, lipid and androgen metabolism disorders are known to be important risk factors in the development of GDM in women with PCOS 41 . Because of this close relationship, PCO appearance in patients with GDM is thought to be between 41 and 52% ratio 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have shown otherwise 37 , the incidence of GDM, pregnancy-related hypertension and neonatal hypoglycemia is higher in women with PCOS diagnosed [38][39][40] . Glucose, lipid and androgen metabolism disorders are known to be important risk factors in the development of GDM in women with PCOS 41 . Because of this close relationship, PCO appearance in patients with GDM is thought to be between 41 and 52% ratio 42 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SHBG is implicated in several pregnant complications. Firstly, SHBG is a marker in predicting GDM in PCOS subjects 18 . Moreover, a previous prospective study reports that SHBG is an independent risk factor for PCOS women who had preeclampsia (PE) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS and GDM were more likely to have impaired fasting blood glucose or impaired glucose tolerance at 18 months post-delivery compared with women that only exhibited GDM (29). Furthermore, hyperandrogenism with accompanying anovulation is one of the main features of PCOS and a previous study has demonstrated that patients with PCOS had lower levels of free androgen and sex hormone-binding globulin (SHBG) compared with patients without GDM (30). A previous study also demonstrated that obese women with PCOS and low SHBG levels were more likely to develop GDM compared with those with high SHBG levels (31).…”
Section: Discussionmentioning
confidence: 99%